1999
DOI: 10.1177/1359104599004001009
|View full text |Cite
|
Sign up to set email alerts
|

Working with Bosnian Medical Evacuees and their Families: Therapeutic Dilemmas

Abstract: This article outlines some key elements of therapeutic work with a group of Bosnian medical evacuees and their families. The unusual feature of this work has been the fact that the clients had not requested any psychological assistance and the therapist had to adapt to this fact and develop ways of dealing with it. The approach followed emphasizes the importance of 'therapeutic presence' instead of imposing formal psychotherapy, and is characterized by an avoidance of psychologizing the evil nature of war atro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 2 publications
1
26
0
1
Order By: Relevance
“…There is some evidence that immigration stressors or social stressors, such as discrimination, are associated with PTSD symptoms in refugee youth [15,30]. Therefore refugee youth may benefit from multiple levels of services, ideally integrated [31,32]. The focus of this article is on the mental and behavioral health component of services for refugee youth.…”
Section: Considerations In the Treatment Of Refugee Youthmentioning
confidence: 99%
“…There is some evidence that immigration stressors or social stressors, such as discrimination, are associated with PTSD symptoms in refugee youth [15,30]. Therefore refugee youth may benefit from multiple levels of services, ideally integrated [31,32]. The focus of this article is on the mental and behavioral health component of services for refugee youth.…”
Section: Considerations In the Treatment Of Refugee Youthmentioning
confidence: 99%
“…severe interpersonal traumas; Steenkamp, Dickstein, Salters-Pedneault, Hofmann, & Litz, 2012) or in certain populations, such as refugees (Sleijpen et al, 2013). Here, it has been suggested that it may be inappropriate to consider mental health problems as evidence of lack of resilience, with the presence of some psychological symptoms considered to be a normative reaction to extreme experiences or circumstances (Papadopoulos, 1999; Sleijpen et al, 2013; Southwick, Bonanno, Masten, Panter-Brick, & Yehuda, 2014). Varying definitions of resilience thus reflect different patterns of adaptive functioning, by different criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the phase of survival is followed by another period, that of adjustment which refers to the most difficult time after they arrive in the receiving country to begin their new lives. The expectations and high hopes are often crashed by the harsh reality that is filled by disorientation, helplessness, bitterness, anger, and ambivalence towards the refugee workers and all other agencies that try to help them (Papadopoulos, 1999a). Moreover, conflict and rivalry among aid organizations and services may make them pawns in other battles of a different nature where the rules are less graspable than open warfare.…”
Section: Devastating Events Survivalmentioning
confidence: 99%
“…The therapists' systems include the actual services and institutions where they are employed, along with their policies and practices, the ideologies of the aid industry, professional affiliations, therapeutic orientation, as well as their own personal background and history. Finally, systemic approaches are useful in working with refugees because they can sharpen the professionals' epistemological sensitivity and inform them about the interaction of the various narratives that each one of these systems uses to express itself (Papadopoulos, 1999a;Sveaass and Reichelt, 2001;Woodcock, 2001). …”
Section: Introduction: Refugees and Systemsmentioning
confidence: 99%
See 1 more Smart Citation